CARCInoeMBRYonIC AnTIGen (CEA) DI KANKER KOLOREKTAL - Nur Rahmi Raehaan; Asvin Nurulita; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Colorectal cancer is a common gastrointestinal malignancy of the colon and rectum. According to the American Society of Clinical Oncology (ASCO) in 2006, preoperative CEA level is useful in dtermining the tumour stage, plan of action and monitoring therapeutic response during the active treatment. Several factors which influence CEA level in patients with colorectal cancer is the staging and the degree of tumour, liver function, and as well as its location. This retrospective study is aimed to know the preoperative CEA levels in 51 patients with colorectal cancer and to compare the levels of CEA based on tumour stage, degree of tumour based on histopathology and tumour location.. This study was carried out at the Dr.Wahidin Sudirohusodo Hospital (RSWS), Makassar during January 2009−December of 2011. The researchers found a significant difference between the levels of CEA with the tumour stage (p=0.000) and its relation with the degree of the tumour (p=0.002), however, based on the tumour location (p=0.585) there was no significant difference between the levels of CEA. In conclusion, it was found that the higher the tumour stage, the higher the levels of the produced CEA. A well differentiated tumour of colorectal cancer produced a higher level of CEA compared to the moderate or poor-differentiated tumours.